Estimating the Economic Value of Narwhal and Beluga Hunts in Hudson Bay, Nunavut - Hoover, Carie; Bailey, Megan; Higdon, Jeff; Ferguson, Steven H.; Sumaila, Rashid (ARCTIC, 2013)
Hunting of narwhal (Monodon monoceros) and beluga (Delphinapterus leucas) in Hudson Bay is an important activity, providing food and income in northern communities, yet few studies detail the economic aspects of these hunts. We outline the uses of narwhal and beluga and estimate the revenues, costs, and economic use value associated with the hunt on the basis of the harvests in 2007. We also explore the effects of cost sharing and inclusion of opportunity cost of labour on model outputs. For the communities participating in each hunt, the average economic use value was negative (-$9399) for beluga and positive ($133 278) for narwhal. The corresponding per capita value estimates were -$1 for beluga and $44 for narwhal. Including the effects of costEvaluation of a Technique to Trap Lemmings Under the Snow sharing with one other hunting activity in the model increased the economic use values to $266 504 for beluga and $321 500 for narwhal. Narwhals provide a higher value per whale, in addition to a higher per capita total economic value to the community, compared to belugas because resources are shared among fewer communities. However, the beluga hunt overall provides greater revenue because more belugas are harvested. In keeping with literature on other hunting activities in the Arctic, our results indicate that the value of whales to communities is largely due to their food value. Dans la baie d’Hudson, la chasse au narval (Monodon monoceros) et au béluga (Delphinapterus leucas) représente une activité importante en ce sens qu’elle est à la fois une source de nourriture et de revenu pour les collectivités du Nord. Pourtant, peu d’études se penchent sur les aspects économiques de cette activité. Nous faisons mention des utilités du narval et du béluga, puis nous estimons les revenus, les coûts et la valeur utilitaire économique liée à ces activités de chasse en fonction des récoltes de 2007. De plus, nous explorons les effets du partage des coûts et de l’inclusion du coût de substitution de la main-d’oeuvre à ...